A Comprehensive Simulation of PEV Penetration Impact on Residential Area Distribution Network - Kevin Gausultan Hadith Mangunkusumo; Joko Hartono (Universitas Ahmad Dahlan, 2023)
Nowadays, rapid growth of electric vehicles is one of the breakthroughs for the future. Electrical utility with first stage of EV ecosystem adoption has to prepare for the impact of high demand of PEV penetration especially in residential area. High number of private charging points in residential area is a big future demand that needs to be considered. This study aims to create a comprehensive model of electric vehicle charging penetration impact in residential area with the worst possible conditions and specific data in Indonesia. Thus the grid operator can prepare for the future impact of the PEV charging in residential area. PEV charging profile and real residential load profile in Indonesia are recorded and used in this study. Driving behavior survey, distribution network modelling and PEV charging profile modelling are constructed. High PEV penetration feeder loading and voltage drop are evaluated. High PEV penetration would impact on overloading and voltage drop on the network. Uniformly distributed load has the highest loading 129.4%, on the other the highest voltage drop 0.87p.u. happen in the centralized load distribution model. Peak shifting in distribution network happen following the EV user charging behavior 17:45 shifted to 20:30. However, for the first stage EV ecosystem development, the time shifted strategy including varying the PEV charging location near the transformer could resulting valley filling and reducing the total network loses.